A photosensitivity reaction to phenobarbital after taking ibuprofen - S. S. Postnikov; M. N. Kostileva; E. S. Ilina; T. A. Finogenova; M. A. Ostrovskaya (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
The paper presents a description of a rare serious adverse reaction to the phenobarbital - photosensitivity. The reaction occurred after use taking ibuprofen in a child aged 1 year. After treatment child was discharged from the hospital after 1 month.